Costs of meals and parking for parents of hospitalised children in an Australian paediatric hospital - Siffleet, J.; Munns, Ailsa; Shields, Linda (Cambridge Publishing, 2010)
Costs to parents of hospitalised children have been extensively explored, from financial costs to psychological, social and emotional costs. No matter what perspective is taken an admission to hospital of a child means added cost to any family’s budget. For those whose income is dependent on a low wage, or welfare, costs of such an event take up a larger proportion of an income than for families from well-to-do backgrounds. In this paper, we explore the potential impact on a family budget of costs of parking and meals incurred during a child’s admission to hospital.To determine costs, a survey was conducted at food outlets to examine types and availability of meals, opening times, proximity to wards and the cost of average types of meals on offer at different facilities. Costs of parking were determined. We took income figures for a family from the website of the Australian Bureau of Statistics (ABS). An estimate of the costs of food and parking to support one parent to remain with the child was at least 30% of the average weekly family disposable income. For one-parent families, their income is significantly proportionally depleted by covering costs of food and parking for an accompanying parent. We recommend that parents be provided with meals whilst staying with their hospitalised child; that provision be made to allow families to eat together and that free parking be made available to all parents.